Composite nanofiltration membrane with surface enhanced Raman detection function and drug separation detection application thereof
By constructing a metal polyphenol network layer on the nanofiltration membrane and growing silver nanoparticles, a composite nanofiltration membrane with surface-enhanced Raman detection function was prepared, which solved the problem of separation and detection of harmful substances in the preparation of drugs, achieved integration of separation and detection, and improved detection efficiency and sensitivity.
Patent Information
- Application Number
- CN202411904631.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to effectively remove harmful substances such as N-nitrosodimethylamine and N-nitrosodiethylamine during drug preparation and to achieve in-situ detection.
A composite nanofiltration membrane with surface-enhanced Raman detection function is adopted. This membrane realizes the integration of drug separation and detection by constructing a metal polyphenol network layer on the porous support membrane and growing silver nanoparticles in situ on it.
It realizes efficient separation between drugs and harmful substances, and uses surface enhancement Raman detection to quickly detect and separate separation effect, simplifies the detection process and improves detection sensitivity.
Smart Images

Figure CN119656893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane technology, and in particular to a composite nanofiltration membrane with surface enhanced Raman detection function and its application in drug separation and detection. Background Art
[0002] Hypertension is one of the most common diseases currently, and its treatment is drug therapy. Irbesartan is the first drug for the treatment of primary hypertension, but during its preparation process, it produces harmful substances such as nitrosamines, such as N, nitrosodimethylamine and N, nitrosodiethylamine. Therefore, how to separate harmful substances from drugs during the pharmaceutical process and detect the separation effect in situ is a shortcoming of the current existing technology.
[0003] Nanofiltration is a pressure-driven membrane separation process between ultrafiltration and reverse osmosis. It is an important membrane separation technology. Compared with traditional separation technologies, it has the advantages of low energy consumption, no secondary pollution, simple operation, and efficient separation. It has broad application prospects in the fields of drug separation, sewage treatment, and seawater desalination. The pore size of the nanofiltration membrane is between 0.5-2nm, and the surface is charged, and ions can be separated according to the size or charge of the ions. For example, CN111203107A discloses a polyphenol-iron nanofilm and its preparation method and application. The porous support membrane is immersed in a polyphenol aqueous solution, a ferrous salt aqueous solution is added, and the co-deposition is shaken, and the reaction is continued at 70°C to obtain a polyphenol-iron nanofilm. The film prepared by this method can not only screen monovalent and multivalent ions in the aqueous solution, but also achieve efficient interception of dye molecules in organic solvents. However, the film prepared by this invention can only achieve separation performance, and cannot achieve surface enhanced Raman detection function.
[0004] Surface enhanced Raman (SERS) can realize in-situ detection, which can reflect the structural information of molecules. A Raman substrate is constructed on the nanofiltration membrane, and Raman detection is performed on the separated nanofiltration membrane to determine whether the harmful substances are removed according to the position of the characteristic peak. CN106731885A discloses a metal organic framework-metal nano-ion composite filter membrane and its preparation method and application. The prepared metal nanoparticles are assembled onto the membrane substrate through chemical bonds, and a metal organic framework is grown in situ on the surface of the metal nanoparticles to obtain a metal organic framework-metal nano-ion composite filter membrane. The composite filter membrane prepared by the method is subjected to the adsorption of organic pollutants by the injection filtration method, and finally directly subjected to surface enhanced Raman detection. The invention uses a metal organic framework to achieve the adsorption of organic pollutants, and then uses metal nanoparticles for surface enhanced Raman detection. Although this method can directly enhance surface Raman detection, complex metal organic framework materials need to be used in conjunction with the membrane product, and industrial application is limited.
[0005] Compared with the adsorption effect of membranes, membrane filtration technology does not require the addition of chemical agents, thus avoiding secondary pollution, being more environmentally friendly, and easier to clean and regenerate.
[0006] The present invention prepares a composite nanofiltration membrane with surface enhanced Raman detection function based on nanofiltration separation technology and surface enhanced Raman detection method, thereby realizing the integration of drug separation and detection. Summary of the invention
[0007] [Technical issues]
[0008] In order to solve the above problems, the present invention provides a composite nanofiltration membrane with surface enhanced Raman detection function, and the composite nanofiltration membrane uses a MPN membrane with simple process, and does not need to construct a complex organic skeleton structure.
[0009] [Technical solution]
[0010] The object of the present invention is to provide a method for preparing a composite nanofiltration membrane with surface enhanced Raman detection function, comprising the following steps:
[0011] (1) soaking the porous support membrane in a polyphenol solution for a period of time, then adding a ferrous salt solution and shaking and co-depositing in a shaker for a period of time, and finally subjecting it to a heat treatment for further reaction to obtain a metal polyphenol network layer (MPN layer);
[0012] (2) immersing the film having the MPN layer in a silver nitrate solution A for a certain period of time to obtain an MPN film with pre-grown silver seeds;
[0013] (3) transferring the MPN membrane with pre-grown silver seeds to the silver nitrate solution B, soaking it for a suitable time, then soaking the membrane in a reducing agent solution to reduce the silver ions to silver nanoparticles, and then washing it to obtain an Ag@MPN composite membrane;
[0014] The mass concentration of the silver nitrate solution B is greater than or equal to the mass concentration of the silver nitrate solution A.
[0015] In one embodiment of the present invention, the porous support membrane includes polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, hydrolyzed polyacrylonitrile ultrafiltration membrane, cellulose acetate ultrafiltration membrane, etc. Polyacrylonitrile ultrafiltration membrane is preferred, and the porous support membrane is a porous support membrane washed with deionized water.
[0016] In one embodiment of the present invention, the polyphenol is one or more of tannic acid, dopamine, phytic acid, gallic acid, quercetin, pyrogallic acid, and epigallocatechin gallate, preferably tannic acid.
[0017] In one embodiment of the present invention, the reducing agent is sodium borohydride, sodium citrate, dimethylamine borane, ascorbic acid, etc. Dimethylamine borane is preferred.
[0018] In one embodiment of the present invention, in step (1), the immersion time of the polyphenol solution is 0 to 60 minutes, and is not 0; preferably 5 minutes.
[0019] In one embodiment of the present invention, in step (1), the time of the co-deposition by oscillation is 60 to 360 minutes. Furthermore, the time of the co-deposition is preferably 120 to 360 minutes.
[0020] In one embodiment of the present invention, in step (1), the temperature of the oscillating co-deposition is 10-60°C, and further, the temperature is preferably 25°C.
[0021] In one embodiment of the present invention, in step (1), the heat treatment temperature is 30-80°C, and the reaction time is 0-60 minutes. Furthermore, the heat treatment temperature is 70°C, and the reaction time is preferably 10 minutes.
[0022] In one embodiment of the present invention, in step (1), the concentration of the polyphenol aqueous solution is 0.8 to 80 mg / mL. Further, the concentration of the polyphenol aqueous solution is preferably 0.8 to 8 mg / ml. Further preferably, it is 4 to 8 mg / ml.
[0023] In one embodiment of the present invention, in step (1), the concentration of the ferrous salt aqueous solution is 0.98 to 98 mg / mL. Further, the concentration of the ferrous salt aqueous solution is preferably 9.8 to 98 mg / ml.
[0024] In one embodiment of the present invention, in step (1), the molar ratio of polyphenol to ferrous salt is 1:1 to 1:100. Further, the molar ratio of polyphenol to ferrous salt is preferably 1:10 to 20.
[0025] In one embodiment of the present invention, in step (2), the concentration of the silver nitrate solution A is 5 to 20 mmol / L, more preferably 5 to 10 mmol / L.
[0026] In one embodiment of the present invention, in step (2), the pre-immersion time is 0 to 30 minutes, and is not 0. Further, the immersion time is preferably 5 to 15 minutes, and further preferably 5 to 10 minutes.
[0027] In one embodiment of the present invention, in step (3), the concentration of the silver nitrate solution B is 10 to 50 mmol / L, more preferably 10 to 25 mmol / L.
[0028] In one embodiment of the present invention, in step (3), the soaking time is 0 to 150 min, and is not 0. Furthermore, the soaking time is preferably 15 to 30 min.
[0029] In one embodiment of the present invention, in step (3), the concentration of the reducing agent dimethylamine borane solution is 0.01 to 0.5 mmol / L. Further, the concentration of the dimethylamine borane solution is preferably 0.01 to 0.1 mmol / L.
[0030] In one embodiment of the present invention, in step (3), the reaction time is 0 to 120 min, and is not 0. Further, the reaction time is preferably 15 to 45 min, and further preferably 15 to 30 min.
[0031] In one embodiment of the present invention, the polyphenol aqueous solution is obtained by dissolving polyphenol in ultrapure water.
[0032] In one embodiment of the present invention, the ferrous salt aqueous solution is obtained by dissolving ferrous salt in ultrapure water.
[0033] In one embodiment of the present invention, the silver nitrate solution is obtained by dissolving silver nitrate in ultrapure water.
[0034] In one embodiment of the present invention, the reducing agent solution is obtained by dissolving dimethylamine borane in ultrapure water.
[0035] In one embodiment of the present invention, MPN is a three-dimensional stable metal polyphenol network composed of polyphenols and metal ions coordinated and assembled, which can be constructed within one minute and can construct a separation layer. The formed metal polyphenol coordination bond has the advantages of strong coordination, structural diversity, hydrolysis stability and pH dependence. Since the catechol structure in the polyphenol can interact through covalent / non-covalent interactions, it gives the metal network universal adhesion properties, and can adhere to the surface of materials with different morphologies and sizes, so that the coating and various supporting base membrane interfaces are stably combined.
[0036] In one embodiment of the present invention, surface enhanced Raman is a special Raman scattering phenomenon that only occurs on the surface of special materials, usually Ag and Au. The generation and quality of SERS signals are affected by the size, morphology and particle spacing of the nanoparticles. A high-intensity local electric field is generated between the noble metal nanoparticles, i.e., a surface enhanced Raman hotspot. When a molecule is in the hotspot, strong Raman scattering will occur.
[0037] In one embodiment of the present invention, a metal polyphenol network is constructed on a porous support membrane to give the film separation performance, and silver nanoparticles are in situ grown on the MPN layer to give the film surface enhanced Raman detection performance.
[0038] The present invention prepares and provides a composite nanofiltration membrane with surface enhanced Raman detection function based on the above method.
[0039] The present invention also provides the application of the composite nanofiltration membrane with surface enhanced Raman detection function in separation and detection in the field of medicine based on nanofiltration technology.
[0040] Beneficial effects:
[0041] (1) The present invention can realize the integration of separation and detection, which makes it possible to separate drugs from harmful substances and quickly detect the effectiveness of separation in situ during the pharmaceutical process, without the need for sample processing steps, thus simplifying the detection process. This detection method can maintain the integrity and original characteristics of the sample, providing a reliable option for rapid analysis. The surface enhanced Raman detection method can accurately detect trace target substances in samples and can improve the detection rate of harmful substances in drugs.
[0042] (2) The present invention adopts in-situ growth of silver nanoparticles, which enhances the coupling between the silver nanoparticles and the base film, thereby enhancing the stability of the base and ensuring the reliability and uniformity of the signal. The detection sensitivity is improved by adjusting the reaction conditions such as the concentration and immersion time of the silver nitrate solution and the reduction time of dimethylamine borane.
[0043] (3) The material process used in the present invention is simple and convenient for industrial application. At the same time, the materials used are non-toxic, the reaction process is carried out in an aqueous solution, and no harmful substances are introduced during the preparation of the substrate, which can ensure the safety during the separation and detection process.
[0044] The present invention adopts nanofiltration separation technology and surface enhanced Raman detection method, improves separation efficiency, shortens detection time, does not require preparatory work in the early stage, and can realize real-time in-situ detection in the pharmaceutical process. In addition, the surface enhanced Raman detection method can realize trace detection of target objects and improve detection sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is the scanning electron microscope image of Ag@MPN composite film;
[0046] Figure 2 This is the surface enhanced Raman spectra of irbesartan, N-nitrosodimethylamine and N-nitrosodiethylamine methanol solutions;
[0047] Figure 3 This is the Raman enhancement test result of the composite membrane after separation by doping different concentrations of N-nitrosodimethylamine and N-nitrosodiethylamine in irbesartan solution. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.
[0049] The reagents used in the embodiments of the present invention are as follows: tannic acid (Tannic acid), Sigma-Aldrich (USA); iron (II) chloride tetrahydrate (Iron (II) chloride tetrahydrate), Sinopharm Chemical Reagent Co., Ltd.; silver nitrate (AgNO3), Sinopharm Chemical Reagent Co., Ltd.; dimethylamine borane (Dimethylamine Borane), Shanghai Myrrel Biochemical Technology Co., Ltd.
[0050] The porous support membrane used in each embodiment of the present invention is a three-dimensional polyacrylonitrile ultrafiltration membrane (PAN, MWCO=40KDa) produced by Beijing Ande Membrane Separation Technology Co., Ltd.
[0051] The composite nanofiltration membrane prepared by the present invention is used for separation and detection of irbesartan drugs. The flux and surface enhanced Raman characteristic peak distribution and the intensity of the characteristic peak are two important parameters for evaluating the separation and detection performance of the nanofilm.
[0052] The parameters selected dead-end filtration operation mode and Raman detection method were used to evaluate the organic phase nanofiltration performance of the composite membrane. Before the test, the composite membrane was pre-pressed for 30 minutes using methanol as the raw material liquid to stabilize its performance. A 1g / L irbesartan methanol solution doped with 100mg / L N-nitrosodimethylamine and 100mg / L N-nitrosodiethylamine was used as the raw material liquid, and the filtration performance test was carried out at a pressure of 0.3MPa. The permeation flux of the composite membrane was recorded to evaluate the organic phase nanofiltration performance of the composite nanofiltration membrane. The composite membrane was subjected to Raman detection, and the characteristic peak distribution and intensity were recorded to evaluate the effectiveness of separation and the retention performance of the composite nanofiltration membrane.
[0053] Among them, the permeation flux (J) of the composite membrane is defined as:
[0054] J=V / (A×t×ΔP) (1)
[0055] Where, V represents the volume of the filtrate, in L; A represents the test area of the nanocomposite membrane, in m 2 , t represents the time required to collect the corresponding filtrate, the unit is h, ΔP represents the pressure applied on the surface of the nanocomposite membrane, the unit is bar, (1 MPa = 10 bar).
[0056] Among them, the separation factor (S) of the composite membrane is defined as:
[0057]
[0058] Among them, C H,p and C H,f Indicates the concentration of harmful substances (N, nitrosodimethylamine and N, nitrosodiethylamine) in the permeate and feed liquid, C I,p and C I,f It represents the concentration of irbesartan in the permeate and feed solution.
[0059] Example 1
[0060] (1) Weigh an appropriate amount of tannic acid and dissolve it in 30 mL of ultrapure water to obtain a polyphenol aqueous solution with a polyphenol concentration of 8 mg / mL; weigh an appropriate amount of ferrous chloride tetrahydrate and dissolve it in 30 mL of ultrapure water to obtain a ferrous salt aqueous solution with a ferrous chloride concentration of 9.8 mg / mL. Immerse the polyacrylonitrile ultrafiltration membrane in the polyphenol aqueous solution for 5 minutes; then add the ferrous salt aqueous solution and quickly move it into a water bath constant temperature oscillator, shake and co-deposit it in a 25°C water bath for 120 minutes; after the co-deposition is completed, move it into an oven and react at 70°C for 10 minutes. Finally, take out the membrane and wash it with ultrapure water to obtain a membrane with an MPN layer.
[0061] (2) Weigh an appropriate amount of silver nitrate and dissolve it in 30 mL of ultrapure water to obtain a 0.01 mol / L silver nitrate solution. Immerse the membrane obtained in step (1) in the silver nitrate aqueous solution for 5 min to grow silver seeds on the MPN layer in advance.
[0062] (3) Weigh an appropriate amount of silver nitrate and dissolve it in 30 mL of ultrapure water to obtain a 0.025 mol / L silver nitrate solution. Immerse the membrane obtained in step (2) in the silver nitrate solution for 30 min.
[0063] (4) Weigh an appropriate amount of dimethylamine borane and dissolve it in 850 mL of ultrapure water to obtain a 0.1 mmol / L dimethylamine borane solution. Immerse the membrane obtained in step (3) in the dimethylamine borane solution to reduce silver ions and achieve in-situ growth of silver nanoparticles. Finally, take out the membrane and wash it with ultrapure water to obtain an Ag@MPN composite membrane.
[0064] Figure 1 It shows that Ag@MPN composite film was successfully synthesized.
[0065] Figure 2 It shows that by preparing Ag@MPN composite film for Raman testing, the three substances can be distinguished by the position of the characteristic peaks. It can also be seen that the deposited MPN layer has no Raman peak and has no effect on the surface enhanced Raman detection of the target object.
[0066] Embodiments 2 to 6
[0067] The concentration of tannic acid in the solution was adjusted (as shown in Table 1), and the other implementation conditions were the same as in Example 1 to obtain an Ag@MPN composite membrane.
[0068] The Ag@MPN composite films prepared in Examples 2 to 6 were tested. The results are shown in Table 1.
[0069] Table 1 Flux and separation factor results of Ag@MPN composite membranes prepared in Examples 1 to 6
[0070]
[0071] It can be seen from the data in Table 1 that as the concentration of tannic acid increases, the pH value in the reaction solution decreases because the tannic acid solution is an acidic substance, which leads to an increase in the flux of the MPN separation layer and a continuous decrease in the separation factor.
[0072] Embodiments 7 to 11
[0073] The concentration of ferrous chloride in the solution was adjusted (as shown in Table 2), and the other implementation conditions were the same as in Example 1 to obtain an Ag@MPN composite membrane.
[0074] The Ag@MPN composite films prepared in Examples 7 to 11 were tested. The results are shown in Table 2.
[0075] Table 2 Flux and separation factor results of Ag@MPN composite membranes prepared in Examples 7 to 11
[0076]
[0077] It can be seen from the data in Table 2 that as the concentration of ferrous chloride increases, the formed Ag@MPN composite membrane becomes denser, resulting in a decrease in the flux of the composite membrane and a continuous increase in the separation factor until it stabilizes.
[0078] Examples 12 to 16
[0079] The co-deposition time was adjusted (as shown in Table 3), and the other implementation conditions were the same as in Example 1 to obtain an Ag@MPN composite film.
[0080] The Ag@MPN composite films prepared in Examples 12 to 16 were tested. The results are shown in Table 3.
[0081] Table 3 Flux and separation factor results of Ag@MPN composite membranes prepared in Examples 12 to 16
[0082]
[0083] It can be seen from the data in Table 3 that with the extension of deposition time, the flux of the composite membrane decreases, which is due to the continuous increase in the thickness of the separation layer; the drug separation factor continues to increase with the long deposition time, on the one hand, due to the complete formation and density of the separation layer, and on the other hand, the density of the separation layer remains unchanged while the thickness increases, which makes the separation factor continue to increase.
[0084] Embodiments 17 to 19
[0085] The concentration of the silver nitrate solution in step (2) was adjusted (as shown in Table 4), and the remaining implementation conditions were the same as in Example 1.
[0086] The Ag@MPN composite films prepared in Examples 17 to 19 were tested. The results are shown in Table 4.
[0087] Table 4 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 17 to 19
[0088]
[0089] The surface enhanced Raman detection excitation wavelength is 532nm, the excitation power is 1mW, and the excitation time is 10s. -1 The absorption peak at is the NC and NN stretching vibration of the tetrazole ring in irbesartan. Since the absorption peak intensity here is the highest, it is selected as the representative of the characteristic peak intensity.
[0090] It can be seen from the data in Table 4 that the change in the pre-soaking silver nitrate concentration affects the growth of the silver nanoparticles grown in situ in step (3). As the concentration of the pre-soaking silver nitrate solution increases, the particle size of the silver nanoparticles increases, the flux and separation factor decrease, and the characteristic peak intensity also decreases.
[0091] Examples 19 to 23
[0092] The pre-immersion time of the silver nitrate solution in step (2) was adjusted (as shown in Table 5), and the remaining implementation conditions were the same as in Example 1.
[0093] The Ag@MPN composite films prepared in Examples 19 to 23 were tested. The results are shown in Table 5.
[0094] Table 5 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 19 to 23
[0095]
[0096] It can be seen from the data in Table 5 that with the increase of the pre-immersion time of silver nitrate, the particle size of the silver nanoparticles of the prepared composite membrane will increase accordingly, resulting in a continuous decrease in the flux and separation factor, and a continuous decrease in the intensity of the characteristic peak.
[0097] Embodiments 24 to 27
[0098] The concentration of the silver nitrate solution in step (3) was adjusted (as shown in Table 6), and the remaining implementation conditions were the same as in Example 1.
[0099] The Ag@MPN composite films prepared in Examples 24 to 27 were tested. The results are shown in Table 6.
[0100] Table 6 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 24 to 27
[0101]
[0102] It can be seen from the data in Table 6 that the MPN layer has good separation performance and can effectively separate drugs and harmful substances, and the separation factor can reach more than 95%. When the silver nitrate solution is at a low concentration, the silver nanoparticles on the membrane surface have a small diameter and a large particle spacing, showing a higher flux; increasing the concentration of the silver nitrate solution, the silver nanoparticles on the composite membrane surface increase in diameter, resulting in an increase in the thickness of the composite membrane, and the silver nanoparticles may block the membrane pores, thereby reducing the flux of the composite membrane. It can be seen from the table that the characteristic peak intensity of irbesartan shows a lower intensity at low concentrations or high concentrations. Because the silver nanoparticles are too large or too small, sufficient Raman hotspots cannot be generated between the silver nanoparticles, which will reduce the Raman detection signal.
[0103] Embodiments 28 to 30
[0104] The immersion time of the silver nitrate solution in step (3) is adjusted, and the other implementation conditions are the same as those in Example 1.
[0105] The Ag@MPN composite films prepared in Examples 28 to 30 were tested. The results are shown in Table 7.
[0106] Table 7 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 28 to 30
[0107]
[0108] From the data in Table 7, it can be seen that as the immersion time increases, the flux continues to decrease. This is because the silver nanoparticle size continues to increase, the thickness of the composite membrane increases, and the membrane pores may be blocked. The intensity of the characteristic peak shows a trend of first increasing and then decreasing. This is because the immersion time is extended, the silver nanoparticle size on the surface of the composite membrane is too large or too small, and sufficient hot spots cannot be generated between the particles, which will reduce the Raman detection signal.
[0109] Examples 31 to 34
[0110] The concentration of the reducing agent dimethylborane in step (3) was adjusted, and the remaining implementation conditions were the same as in Example 1.
[0111] The Ag@MPN composite films prepared in Examples 31 to 34 were tested. The results are shown in Table 8.
[0112] Table 8 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 31 to 34
[0113]
[0114] It can be seen from the data in Table 8 that with the increase of dimethylborane concentration, the particle size of silver nanoparticles increases accordingly, which may block the membrane pores, resulting in a decrease in the flux of the composite membrane and a continuous decrease in the separation factor; the particle size of silver nanoparticles affects the generation of Raman hotspots, and the characteristic peak intensity shows a trend of first increasing and then decreasing.
[0115] Embodiments 35 to 39
[0116] The reduction time of the reducing agent dimethylborane in step (3) was adjusted, and the remaining implementation conditions were the same as in Example 1.
[0117] The Ag@MPN composite films prepared in Examples 35 to 39 were tested. The results are shown in Table 9.
[0118] Table 9 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 35 to 39
[0119]
[0120] It can be seen from the data in Table 9 that as the reduction time increases, the particle size of silver nanoparticles increases at any time, which may clog the pores, resulting in a continuous decrease in flux and separation factor; the change in the particle size of silver nanoparticles cannot produce enough Raman hotspots, resulting in a decrease in the intensity of the characteristic peak.
[0121] Examples 40-43 Separation and quantitative detection of genetically harmful substances such as nitrosamines based on Ag@MPN composite membrane
[0122] (1) The Ag@MPN composite film was prepared according to the method in Example 1.
[0123] (2) Separation and quantitative detection of genetically harmful substances such as nitrosamines based on the Ag@MPN composite membrane:
[0124] Before testing, the composite membrane must be pre-pressed for 30 minutes using methanol as the raw material liquid to stabilize its performance.
[0125] A 1 g / L irbesartan methanol solution doped with different concentrations of N-nitrosodimethylamine and N-nitrosodiethylamine was used as the raw material solution and filtered at a pressure of 0.3 MPa. The composite membrane was then subjected to Raman detection. The results are shown in Table 10.
[0126] Table 10 Flux, separation factor and characteristic peak intensity results of Ag@MPN composite membranes prepared in Examples 40 to 43
[0127]
[0128] It can be seen from the data in Table 10 that the Ag@MPN composite membrane prepared by this method has good separation performance, and has excellent separation performance for harmful substances at low concentrations.
[0129] The concentration of harmful substances (10-200 mg / L) was linearly fitted with the corresponding Raman peak intensity. The results are as follows: Figure 3 As shown. Figure 3 It can be seen from the figure that when different concentrations of harmful substances (N-nitrosodimethylamine and N-nitrosodiethylamine) are doped in the irbesartan solution, as the concentration of the doped harmful substances decreases, the intensity of the Raman characteristic peak decreases, and the concentration of the harmful substances has a good linear relationship with the intensity of the characteristic peak. 2 It is 0.98, which means that this method can be used to achieve quantitative detection of harmful substances in irbesartan, which is convenient for better ensuring the quality of drugs and ensuring the safety of drug use.
[0130] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a composite nanofiltration membrane with surface enhanced Raman detection function, characterized in that: The following steps are involved: (1) The porous support membrane is first immersed in a polyphenol solution, then a ferrous salt solution is added, shaken and co-precipitated, and then heat-treated to obtain a membrane having MPN; (2) immersing the film with the MPN layer in a silver nitrate solution A to obtain an MPN film with pre-grown silver seeds; (3) transferring the MPN membrane with pre-grown silver seeds to a silver nitrate solution B for immersion, and then immersing the membrane in a reducing agent solution to achieve in-situ growth of silver nanoparticles; finally, taking out the membrane and washing it with ultrapure water to obtain a composite nanofiltration membrane; The mass concentration of the silver nitrate solution B is greater than or equal to the mass concentration of the silver nitrate solution A.
2. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the silver nitrate solution A is 5 to 20 mmol / L.
3. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the silver nitrate solution B is 10 to 50 mmol / L.
4. The preparation method according to claim 1, characterized in that: The porous support membrane is one of polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, hydrolyzed polyacrylonitrile ultrafiltration membrane and cellulose acetate ultrafiltration membrane; the polyphenol is one or more of tannic acid, dopamine, phytic acid, gallic acid, quercetin, pyrogallic acid and epigallocatechin gallate; the ferrous salt is one or more of ferrous chloride, ferrous chloride tetrahydrate, ferrous sulfate and ferrous bromide.
5. The preparation method according to claim 1, characterized in that: In step (1), the porous support membrane is immersed in the polyphenol solution for 0 to 60 minutes, and is not 0; the oscillation co-deposition is 60 to 360 minutes, the reaction temperature is 10 to 60°C, the heat treatment temperature is 30 to 80°C, and the reaction time is 0 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the polyphenol aqueous solution is 0.8-80 mg / mL, the concentration of the ferrous salt aqueous solution is 0.98-98 mg / mL, and the molar ratio of polyphenol to ferrous salt is 1:1-1:
100.
7. The preparation method according to claim 1, characterized in that: In step (2), the soaking time is 0 to 30 minutes, and is not 0; in step (3), the soaking time is 0 to 150 minutes, and is not 0.
8. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the reducing agent dimethylamine borane solution is 0.01 to 0.5 mmol / L, and the reaction time is 0 to 120 min, and is not 0.
9. A composite nanofiltration membrane with surface enhanced Raman detection function prepared by the method according to any one of claims 1 to 8.
10. Use of the composite nanofiltration membrane according to claim 9 in drug separation and detection.
Citation Information
Patent Citations
POLYMERIC Membranes CONTAINING FUNCTIONALIZED SiO2 NANOTUBES APPLIED TO WATER NANOFILTRATION AND PREPARATION PROCESSES
BR102015003131A2
Metal organic framework and metal nano ion composite filter membrane and preparation method and application thereof
CN106731885A
Surface enhanced Raman spectrum detection substrate, and preparation method and application thereof
CN109030456A
Preparation of imprinted film based on surface enhanced Raman scattering and selective detection of enrofloxacin hydrochloride in water
CN109731559A
Polyphenol-iron nano-film as well as preparation method and application thereof
CN111203107A